A Review on Natural Adsorbents/ Nano-adsorbents Based on Chitosan for Removal of Metal Contaminants from Water - Mohammad Hossein Noori Shamsi; Mostafa Jafari; Mohammad Shahin (علوم و مهندسی آب و فاضلاب, 2018)
Water contamination is one of the most important challenges involved in the human health and environment. In particular and due to the high growth of industry, the contamination by heavy metals is very worrying and of much concern. Heavy metals can provide the incidence of many dangerous diseases especially different types of cancers. During the recent years, chitosan and chitosan nanoparticles and their derivations have attracted many researches on adsorption of contaminants especially heavy metals, due to their content of OH and NH2 groups, non-toxicity, low cost and availability. In this review paper, preparation of chitosan, chitosan nanoparticles and kinds of modified chitosan have been investigated and their applications in heavy metals adsorption process from aqueous solutions have been briefly outlined. The effect of significant parameters on the adsorption process such as chitosan crystallization, the concentration of adsorbent, the initial concentration of heavy metals, process time, solution pH, and temperature as well as isotherm and adsorption kinetics have been investigated. Then the response surface methodology (RSM) has been explained and common methods for optimizing the adsorption process parameters for heavy metals have been examined. Finally, recycling and reuse of chitosan-based adsorbents in the absorption process have been evaluated.